Preparation of adhesive-free composite boards from agricultural and forestry solid waste: pretreatment-promoted enhancement of wet hot-pressing compatibility - Qiyu Zhang; Jiachen Zuo; Yuanhao Wang; Lin Lu; Hongxing Yang (Bioresource Technology Reports, 2026)

Species-specific effects and trophic transfer of selenium in a freshwater food chain - Hongyan Lin; Yixuan Luo; Lixia Li; Fangli Wu; Hongxing Chen; Lingtian Xie (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Predicting county-level winter wheat yield in Eastern China using multi-source spatiotemporal data: An explainable machine learning approach - Bihui Lu; Kun Yu; Lin Qiu; Huayong Li; Hongxing Wang; Wenyu Zhang; Xiaohong Liu; Jie Shan; Nan Li (Agricultural and Forest Meteorology, 2026)

Tandem synergy of hydroxyl radicals and nonradical ferryl for efficient photo-self-Fenton mineralization of refractory pollutants - Ailing Zhang; Meili Liu; Weiqin Wei; Wenwen Jing; Jiayan Teng; Yuanshen Qin; Lin Jing; Yongfa Zhu; Hongxing Dai; Jiguang Deng; Zhen Wei (Water Research, 2026)

Influence of tropical cyclones on organic aerosols in a coastal city of South China - Hongxing Jiang; Yuanhang Deng; Hai Guo; Yunxi Huo; Dawen Yao; Haoxian Lu; Changliu Wu; Meiyi Fan; Xiaopu Lyu; Fengwen Wang; Yan-Lin Zhang; Fan Zhang; et al. (Atmospheric Research, 2026)

Construction of PtRu/Nb2O5 catalysts with high performance and good water- and chlorine-tolerance for the synergistic oxidative removal of multi-component VOCs - Meiyue Li; Qinpei Sun; Yiwen Jia; Jiguang Deng; Zhiquan Hou; Lu Wei; Zhen Wei; Lin Jing; Liangshi Wang; Yuxi Liu; Hongxing Dai (Journal of Environmental Sciences, 2026)

Experimental and numerical study of a novel thermochromic bifacial photovoltaic glazing system - Chuyao Wang; Man Yi Wong; Hao Zhou; Zhe Song; Kaixin Lin; Hongxing Yang; Jie Ji; Chi Yan Tso (Building and Environment, 2026)

Robust high-temperature macroscale superlubricity enabled by interface engineering of boronized surfaces and hydroxyl-rich polyol lubricants - Yixuan Zhang; Hongxing Wu; Hang Li; Lin Wang; Junqin Shi; Ke Hua; Haifeng Wang; Feng Zhou; Weimin Liu (Science Bulletin, 2026)

Enhanced SO2 resistance of the Pd/Silicate-1 catalyst by rare earth oxide modification in methane combustion - Jinxiong Tao; Hongxia Lin; Yuxi Liu; Jiguang Deng; Lin Jing; Zhiwei Wang; Lu Wei; Zhen Wei; Zhiquan Hou; Zexu Zhang; Hongxing Dai (Journal of Environmental Sciences, 2026)

Spatial-temporal patterns and multi-scale drivers of allergenic pollen Fraxinus, Platanus and Humulus in the urban and suburban area of Beijing, China - Xiaoxin Qin; Jianqin Xu; Yiyin Li; Xiao Yun; Hongxing Zhang; Wenjun Liu; Xinyi Zhao; Nan Lin (Urban Forestry & Urban Greening, 2026)

DDX21 nuclear-cytoplasmic shuttling recruits RPS18 to viral dsRNA to promote CSFV replication - Bingke Li; Bolun Zhou; Chenchen Sun; Shurou Li; Ye Bai; Ruibo Zhao; Yiwan Song; Yintao He; Lin Yi; Hongxing Ding; Shuangqi Fan; Jinding Chen; et al. (Veterinary Microbiology, 2026)

Dual-readout lateral flow immunoassay for detection of amphenicols using intensified colorimetric–fluorescent carbon dots nanocomposite - Hongfang Li; Wenqing Xu; Yina Zhu; Hongxing Wei; Xiaoyue Liu; Lin Li; Guoliang Li (Food Chemistry, 2025)

Temperature-dependent transformation of piggery biogas residue pyrolysis products: Balancing resource recovery and environmental safety - Chunyang Chen; Xiujuan Wang; Hongxing Tu; Qianyi Cai; Junshi Tao; Xiaojun Lin; Jingwen Zeng; Jinrong Qiu; Zifeng Luo (Bioresource Technology, 2025)

Catalytic oxidation of volatile organic compounds over supported noble metal and single atom catalysts: A review - Honghong Zhang; Zhiwei Wang; Hongxia Lin; Yuxi Liu; Hongxing Dai; Jiguang Deng (Journal of Environmental Sciences, 2025)

The role of the ferroptosis pathway in the toxic mechanism of TCDD-induced liver damage in zebrafish - Yunqi Gao; Hongsong Chen; Hua Lian; Xiaoxu Cai; Lingtian Xie; R.G. Ahmed; Xuguang Lin; Hongxing Chen; Wu Dong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Plasmonic nanoheater for formaldehyde degassing - Gaopan Chen; Peng Yu; Lian Yang; Roberto Caputo; Feng Lin; Liang Pan; Yang Gao; Hongxing Xu; Alexander Govorov; Zhiming Wang (Chemical Engineering Journal, 2025)

Enhanced biodegradation of sulfamethazine in swine manure composting: Pathway elucidation, mechanism insights, and optimization of a novel Bacillus sp. strain - Xiaojun Lin; Jingtong Li; Chunyan Chen; Zifeng Luo; Hongxing Tu; Yuwan Pang; Xiujuan Wang; Qianyi Cai; Zebin Wei; Jianfeng Huang; Jingwen Zeng; Jinrong Qiu (International Biodeterioration & Biodegradation, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Effects of combined stressors to TCDD and high temperature on HSP/CYPs signaling in the zebrafish embryos/larvae - Hongsong Chen; Hao Chen; Lian Hua; Yunqi Gao; Yuehua Yao; Yangfan Xu; Jingfeng Yang; Lingtian Xie; Yongju Luo; Ting Huang; Hongxing Chen; Xuguang Lin; et al. (Environmental Pollution, 2025)

Response surface methodology and Box-Behnken design optimization of Sulfaquinoxaline removal efficiency and degradation mechanisms by Bacillus sp. strain DLY-11 - Chunyan Chen; Zifeng Luo; Hongxing Tu; Xiaojun Lin; Yuwan Pang; Jianfeng Huang; Jun Zhang; Xiujuan Wang; Qianyi Cai; Zebin Wei; Jingwen Zeng; Jinrong Qiu (Journal of Hazardous Materials, 2025)

Impact of defatted black soldier fly (Hermetia illucens) larvae meal on health, muscle texture, and intestinal microbiota in Pacific white shrimp (Penaeus vannamei) - Tong Chang; Hongxing Lin; Fenglu Han; Chang Xu; Erchao Li (Aquaculture, 2025)

Bamboo-like MnO2⋅Co3O4: High-performance catalysts for the oxidative removal of toluene - Ali Rastegarpanah; Jiguang Deng; Yuxi Liu; Lin Jing; Wenbo Pei; Jia Wang; Hongxing Dai (Journal of Environmental Sciences, 2025)

Harnessing metal-metal interactions for simultaneously boosting photocatalytic hydrogen and benzaldehyde production - Yajie Feng; Chi Lin; Yifei Huang; Bing Li; Yingxin He; Jiangping Ma; Chaogang Ban; Lujie Ruan; Hongxing Jia; Xiaoping Tao; Liyong Gan; Xiaoyuan Zhou (Chemical Engineering Journal, 2025)

Characterization of the transmembrane C-type lectin reveals a novel phagocytic receptor for hemocytes of Tegillarca granosa - Dan Su; Jie Lin; Yang Zhang; Zexin Yang; Yefeng Lin; Yingbin Xu; Shanjie Zha; Yongbo Bao; Hongxing Liu (Aquaculture, 2024)

Nitrogen and phosphorus recovery from livestock wastewater via magnesium ammonium phosphate precipitation: A critical review of methods, progress, and insights - Jingtong Li; Chunyan Chen; Zifeng Luo; Jinrong Qiu; Li Zhao; Jun Zhang; Xue Xiao; Xiaojun Lin; Xiujuan Wang; Qianyi Cai; Jingwen Zeng; Hongxing Tu; et al. (Journal of Water Process Engineering, 2024)

Optimization of degradation conditions for sulfachlorpyridazine by Bacillus sp. DLY-11 and analysis of biodegradation mechanisms - Xiaojun Lin; Jun Zhang; Zifeng Luo; Jingtong Li; Xue Xiao; Xiujuan Wang; Qianyi Cai; Weida Yu; Junshi Tao; Jingwen Zeng; Hongxing Tu; Jinrong Qiu (Journal of Hazardous Materials, 2024)

The influence of crystal facet on the catalytic performance of MOFs-derived NiO with different morphologies for the total oxidation of propane: The defect engineering dominated by solvent regulation effect - Qianqian Chai; Chuanqiang Li; liyun Song; Cui Liu; Tao Peng; Chuanchuan Lin; Yangyang Zhang; Shimin Li; Qiang Guo; Shaorui Sun; Hongxing Dai; Xuxu Zheng (Journal of Hazardous Materials, 2024)

In situ mass spectrometry imaging reveals pesticide residues and key metabolic pathways throughout the entire cowpea growth process - Shufan Jiang; Jingling Lin; Rui Zhang; Qiong Wu; Hongxing Li; Qun Zhang; Mingyue Wang; Longjun Dai; Defang Xie; Yue Zhang; Xinzhong Zhang; Bingjun Han (Journal of Hazardous Materials, 2024)

Effects of porcine epidemic diarrhea virus infection on CD21+ B cells activation - Chen Yuan; Yidan Lin; Yawen Wang; Yanan Zhang; Xue Zhao; Hongxing Yuan; Tanqing Li; Qinye Song (Veterinary Microbiology, 2024)

PdPtVO /CeO2−ZrO2: Highly efficient catalysts with good sulfur dioxide-poisoning reversibility for the oxidative removal of ethylbenzene - Jia Wang; Yuxi Liu; Jiguang Deng; Lin Jing; Xiuqing Hao; Xing Zhang; Xiaohui Yu; Hongxing Dai (Journal of Environmental Sciences, 2024)

NO production of granulocytes associated with antibacterial immune response in Tegillarca granosa - Hongxing Liu; Sixuan Ding; Yingbin Xu; Jie Lin; Kaiqi Jiang; Shanjie Zha; Yongbo Bao (Fish & Shellfish Immunology, 2024)

In situ biomass burning enhanced the contribution of biogenic sources to sulfate aerosol in subtropical cities - Tingting Li; Jun Li; Luhua Xie; Boji Lin; Hongxing Jiang; Rong Sun; Xiao Wang; Ben Liu; Chongguo Tian; Qilu Li; Wanglu Jia; Gan Zhang; et al. (Science of The Total Environment, 2024)

Regulating catalytic stability of PtSnM/CeO2 (M = Mn, W, Nb) catalysts via the closely coupled multi-active sites to promote multicomponent VOCs oxidation - Ruyi Gao; Xinrong Tian; Xinlei Ding; Zhiquan Hou; Zeya Li; Xiaohui Yu; Jia Wang; Linke Wu; Lin Jing; Jiguang Deng; Yuxi Liu; Hongxing Dai (Chemical Engineering Journal, 2023)

Hemocyte proliferation is associated with blood color shade variation in the blood clam, Tegillarca granosa - Zexin Yang; Xin He; Hongyu Jin; Dan Su; Zhihua Lin; Hongxing Liu; Yongbo Bao (Aquaculture, 2023)

Point defect engineering of elemental phosphorus for photocatalytic hydrogen evolution - Yajie Sun; Xinya Pei; Bo Wang; Yun Hau Ng; Ruixue Zhu; Qichao Zhang; Jiguang Deng; Yuxi Liu; Lin Jing; Hongxing Dai (Chemical Engineering Journal, 2023)

Research on a DC–DC Converter and Its Advanced Control Strategy Applied to the Integrated Energy System of Marine Breeding Platforms - Hongxing Chen; Weiming Lin; Wei He (Journal of Marine Science and Engineering, 2023)
The deep-sea aquaculture industry will become one of the important pillars of the future marine economy. However, the application of clean energy in the new scenario needs to be strengthened for platform operation. For this kind of renewable-energy distributed-generation system, an energy storage system is essential. A bidirectional DC–DC converter is essential for distributed power generation systems. It connects a variety of renewable energy sources with energy storage cells. A high-gain bidirectional Cuk circuit with zero ripple is proposed in the paper. It is characterized by a simple structure, zero ripple, low voltage stress of semiconductor power devices, and high voltage gain. A passivity-based control with linear active disturbance rejection is proposed to solve the problems of the large steady-state error. The zero steady-state error, strong robustness, and whole-range stability have been obtained for the proposed control strategy. Finally, a simulation was carried out. A 100 W, 48 V/400 V prototype was built to verify the validity of the theoretical analysis for the proposed circuit. The improved passivity-based control strategy was verified to solve the contradiction between rapidity and overshoot. It can be realized to improve the dynamic performance of the proposed converter and achieve robust control.

Graphitic carbon nitride-based photocatalysts in the applications of environmental catalysis - Hongxia Lin; Jinmo Wu; Fan Zhou; Xiaolong Zhao; Pengfei Lu; Guanghui Sun; Yuhan Song; Yayun Li; Xiaoyong Liu; Hongxing Dai (Journal of Environmental Sciences, 2023)

An innovative passive sampler to reveal the high contribution of biomass burning to black carbon over Indo-China Peninsula: Radiocarbon constraints - Xiao Wang; Jun Li; Xiangyun Zhang; Zhineng Cheng; Haoyu Jiang; Hongxing Jiang; Boji Lin; Sanyuan Zhu; Shizhen Zhao; Junwen Liu; Chongguo Tian; Ruijie Zhang; et al. (Atmospheric Environment, 2023)

Protective Effects of Salidroside on Lead Acetate-induced Oxidative Stress and Hepatotoxicity in Sprague-Dawley Rats - Chen Chen; Beibei Lin; Shanshan Qi; Jia He; Hongxing Zheng (Biological Trace Element Research, 2019)

The development of transgenic mice for the expression of large amounts of human lysozyme in milk - Xiaojie Wu; Yanli Lin; Yongyi Xi; Zhenlu Shao; Yanrong Zhou; Fang Liu; Hongxing Chen (Biotechnology Letters, 2014)

The high-level accumulation of n-3 polyunsaturated fatty acids in transgenic pigs harboring the n-3 fatty acid desaturase gene from Caenorhabditis briggsae - Yanrong Zhou; Yanli Lin; Xiaojie Wu; Chong Feng; Chuan Long; Fuyin Xiong; Ning Wang; Dengke Pan; Hongxing Chen (Transgenic Research, 2014)

The extremely high level expression of human serum albumin in the milk of transgenic mice - Xiaojie Wu; Yanli Lin; Fuyin Xiong; Yanrong Zhou; Fang Yu; Jixian Deng; Peitang Huang; Hongxing Chen (Transgenic Research, 2012)

Salicylic acid-altering Arabidopsis mutants response to salt stress - Lin Hao; Yan Zhao; Dandan Jin; Ling Zhang; Xiaohua Bi; Hongxing Chen; Qiang Xu; Chunyan Ma; Guangzhe Li (Plant and Soil, 2012)

Plk1-mediated phosphorylation of UAP56 regulates the stability of UAP56 - Fuyin Xiong; Yanli Lin; Zhengbin Han; Gengshou Shi; Liyuan Tian; Xiaojie Wu; Qiangcheng Zeng; Yanrong Zhou; Jixian Deng; Hongxing Chen (Molecular Biology Reports, 2012)

Characterization of Bombyx mori Nucleopolyhedrovirus ORF109 that Encodes a 25-kDa Structural Protein of the Occlusion-Derived Virion - Yang Zhou; Qin Yao; Hongxing Shen; Hengchuan Xia; Feng Lin; Keping Chen (Current Microbiology, 2010)

Efficient production of omega-3 fatty acid desaturase (sFat-1)-transgenic pigs by somatic cell nuclear transfer - DengKe Pan; Li Zhang; YanRong Zhou; Chong Feng; Chuan Long; Xiao Liu; Rong Wan; Jian Zhang; AiXing Lin; EnQiu Dong; ShuChen Wang; HouGang Xu; et al. (Science China Life Sciences, 2010)

Investigating impacts of urban morphology on spatio-temporal variations of solar radiation with airborne LIDAR data and a solar flux model: a case study of downtown Houston - Bailang Yu; Hongxing Liu; Jianping Wu; Wei-Ming Lin (International Journal of Remote Sensing, 2009)